FGF19 promotes progression of prostate cancer. Issue 10 (8th April 2015) - Nagamatsu, Hirotaka; Teishima, Jun; Goto, Keisuke; Shikuma, Hiroyuki; Kitano, Hiroyuki; Shoji, Koichi; Inoue, Shogo; Matsubara, Akio
Abstract : BACKGROUND: Fibroblast growth factor (FGF) signaling pathways have been reported to play important roles in prostate cancer (PCa) progression. FGF19 is one of a subfamily of FGFs that circulate in serum and act in an endocrine manner. Our objective was to investigate its role in the progression of PCa. METHODS: The effect of FGF19 on the proliferation and epithelial–mesenchymal transition of LNCaP and PC3 cells was examined using MTT assay and Western blotting. Serum concentration of FGF19 was measured by ELISA in 209 patients with PCa, and the association between clinicopathological features and the presence of FGF19‐positive cells in tissues derived from 155 patients who undergone radical prostatectomy was investigated. RESULTS: Under androgen‐deprived conditions achieved by incubation in medium with FGF19, the expression of N‐cadherin in LNCaP cells was enhanced, that of E‐cadherin and caspase 3 was suppressed, and the viability of LNCaP and PC3 cells was significantly enhanced. Significantly higher levels of PSA were recorded in the group determined by immunohistochemistry staining to be FGF19‐positive ( P = 0.0046). The 5‐year biochemical recurrence‐free survival rate after radical prostatectomy was 46.4% in the FGF19‐positive group and 70.0% in the FGF19‐negative group ( P = 0.0027). In multivariate analysis, the presence of FGF19‐positive tissues was an independent factor for worse prognosis after radical prostatectomy ( P = 0.0052). Serum FGF19 levels in high Gleason grade group were higher than that in low Gleason grade group ( P = 0.0009). CONCLUSIONS: FGF19 might be associated with biochemical recurrence after radical prostatectomy by promoting cell proliferation and epithelial–mesenchymal transition of PCa. Prostate 75:1092–1101, 2015 . © 2015 Wiley Periodicals, Inc.